The region upstream of the telomerase reverse transcriptase gene is essential for in planta telomerase complementation - Crhák, Tomáš; Zachová, Dagmar; Fojtová, Miloslava; Sýkorová, Eva (Plant science, 2019)
Telomerase is essential for the maintenance of telomeres, structures located at the ends of linear eukaryotic chromosomes that are crucial for genomic stability. Telomerase has been frequently explored in mammals because of its activity in many types of cancers, but knowledge in plants is rather sketchy despite plants representing useful models due to peculiarities in their telomeres and telomerase biology. We studied in planta complementation of telomerase in Arabidopsis thaliana mutant plants with disrupted expression of the gene encoding the telomerase protein subunit (AtTERT) and significantly shortened telomeres. We found that the upstream region of AtTERT, previously identified as a putative minimal promoter, was essential for reconstitution of telomerase function, as demonstrated by the full or partial recovery of the telomere phenotype in mutants. In contrast, transformation by the full length AtTERT gene construct resulted in more progressive telomere shortening in mutants and even in wild type plants, despite the high level of AtTERT transcript and telomerase activity detected by in vitro assay. Thus, the telomerase protein subunit putative promoter is essential for in planta telomerase reconstitution and restoration of its catalytical activity. Contributions from other factors, including those tissue-specific, for proper telomerase function are discussed.
Keywords: proteiny huseníčku; Promoter; in planta; Arabidopsis Proteins; Complementation; promotorové oblasti (genetika); telomerasa; Telomerase; Arabidopsis thaliana; Arabidopsis; Telomere; Promoter Regions, Genetic